2017
DOI: 10.1155/2017/6913564
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Findings of Pulmonary Mycobacterium simiae Infection

Abstract: Nontuberculous mycobacterial (NTM) pulmonary infections can be quite similar to tuberculosis, both clinically and radiologically. However, the treatment protocol is not similar. Mycobacterium simiae is a rare cause of NTM pulmonary infection. Herein, we aimed to evaluate and compare the computed tomography (CT) scan findings of M. simiae infection in lungs. For this reason, thirty-four patients (n = 34) with M. simiae lung infection were retrospectively evaluated. Diagnosis was confirmed by American Thoracic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…As reported elsewhere (7,15), clinical signs of infection among our cohort patients were mostly respiratory symptoms such as productive cough. Our study confirms the findings of van Ingen et al 7, with patients who lost weight being significantly more likely to meet the ATS diagnostic criteria.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As reported elsewhere (7,15), clinical signs of infection among our cohort patients were mostly respiratory symptoms such as productive cough. Our study confirms the findings of van Ingen et al 7, with patients who lost weight being significantly more likely to meet the ATS diagnostic criteria.…”
Section: Discussionsupporting
confidence: 76%
“…Micronodular lesions were the most common radiological findings and were associated with ATS criteria for M. simiae in the multivariate analysis. Cavitary lesions were present in 25.8% of our cohort patients, compared with studies that reported cavitary lesions in 3% to 15% of patients (11,15). Unlike in the study by van Ingen et al 7, cavitary lesions were not associated with ATS criteria for infection in our cohort.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Baghaei et al showed that nodular lesions were found in 100% of patients, and bronchiectasis and cavities in 84% and 88%, respectively [ 15 ]. Furthermore, Baghizadeh et al showed that the most common findings were nodular lesions (100%), and bronchiectasis (85.29%), in addition to other findings such as para-tracheal and hilar lymphadenopathy (44%), pleural effusion (20.6%), and pleural thickening (58.8%) [ 21 ]. In the latter study, the right middle lobe was the most commonly involved (50%), followed by the lingula (47%), and the right upper lobe (41%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Baghizadeh et al showed that the most common findings were nodular lesions (100%), and bronchiectasis (85.29%), in addition to other findings such as para-tracheal and hilar lymphadenopathy (44%), pleural effusion (20.6%), and pleural thickening (58.8%) [ 21 ]. In the latter study, the right middle lobe was the most commonly involved (50%), followed by the lingula (47%), and the right upper lobe (41%) [ 21 ]. On the other hand, Shitrit et al noted cavitary disease in 3%, pulmonary infiltrates in 57%, and pleural effusion in 16%, along with involvement of the middle and lower lobes in 55% [ 1 ].…”
Section: Discussionmentioning
confidence: 99%